2013
DOI: 10.3906/biy-1212-7
|View full text |Cite
|
Sign up to set email alerts
|

Biopotential of Verbesina encelioides (stem and leaf powders) in silver nanoparticle fabrication

Abstract: Nanotechnology has opened new opportunities in the field of medical sciences and pharmaceuticals. Commercially, nanoparticles are in great demand in electronics, catalysis, chemistry, energy, and medicine. Today in nanoparticle production green synthesis, using biological material including medicinal plants as a starting material, is in vogue. In the present investigation the powder extract (stems and leaves) of an important medicinal plant, Verbesina encelioides, was used for the biosynthesis of bionanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Jeeva et al [25] reported moderate antibacterial activity of C. coriaria AgNPs against pathogenic bacteria while Fayaz et al [26] reported enhanced antibacterial activity with antibiotics. Mahitha et al [27] and Kushwaha and Malik [28] reported antibacterial and antifungal activity of Bacopa monniera whole plant and Verbesina enceliodes leaf AgNPs respectively. Antibacterial and antifungal activities of AgNPs from Tephrosia purpurea leaf extract were reported by Ajitha et al [29].…”
Section: Resultsmentioning
confidence: 99%
“…Jeeva et al [25] reported moderate antibacterial activity of C. coriaria AgNPs against pathogenic bacteria while Fayaz et al [26] reported enhanced antibacterial activity with antibiotics. Mahitha et al [27] and Kushwaha and Malik [28] reported antibacterial and antifungal activity of Bacopa monniera whole plant and Verbesina enceliodes leaf AgNPs respectively. Antibacterial and antifungal activities of AgNPs from Tephrosia purpurea leaf extract were reported by Ajitha et al [29].…”
Section: Resultsmentioning
confidence: 99%
“…[7] Many works reported on the uses of plant extracts derived from many species and various parts of plants for the green synthesis of AgNPs including leaf, latex, stem, root and fruit of edible, ornamental and medicinal plants. The examples were holy basil (Ocimum sanctum), [8] garlic (Allium sativum), [9] bamboo (Bambusa arundinacea and Bambusa nutans), [10] Acalypha hispida, [11] Verbesina encelioides, [12] red ball snake gourd (Trichosanthes tricuspidata) [13] and bitter melon (Mo-mordica charantia). [14] The phytochemicals in these plant extracts, such as alkaloids, tannins, phenolics, saponins, terpenoids, proteins, vitamins and polysaccharides, were proposed to serve as reducing agents, while the complex molecules could assist a stabilization of the synthesized AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these methods may successfully produce highly stable and well‐defined AuNPs, they have various drawbacks such as the use of environmentally harmful chemicals and expensive equipment . Therefore, green nanoparticle synthesis by microorganisms and plant extracts has gained considerableNew York City importance in recent years . The green synthesis method is more facile and eco‐friendly, and it does not require rigorous conditions or toxic agents.…”
Section: Introductionmentioning
confidence: 99%